Cecropin AD ameliorates pneumonia and intestinal injury in mice with mycoplasma pneumoniae by mediating gut microbiota - Bowen Li; Mingming Liu; Wenjing Du; Shuaidong Wang; Zekang Xu; Xiaoqian Zhang; Yang Zhang; Song Hua (BMC Veterinary Research)
Abstract Animals infected with mycoplasma pneumoniae not only develop respiratory diseases, but also cause digestive diseases through the lung-gut axis mediated by the intestinal flora, and vice versa. Antimicrobial peptides are characterized by their bactericidal, anti-inflammatory, and intestinal flora-regulating properties. However, the effect of cecropin AD (CAD) against mycoplasma pneumonia remains unclear. To investigate the anti-inflammatory effect of CAD on mycoplasma pneumonia and the associated mechanism, mice were infected with Mycoplasma capricolum subsp. Capripneumoniae(Mccp) to elicit lung inflammation, followed by oral administration of CAD via gavage. The findings showed that mice receiving twice injections of 2.08 × 108 copies of Mccp suffered significant pathological damage to their lungs and colons. Additionally, there was a notable upsurge in inflammatory factors within the affected tissues. 16 S rDNA sequencing revealed alterations in the colonic microbiota, including a decrease in the abundance of beneficial bacteria such as Corynebacterium_glutamicum and Candidatus_Saccharimonas, and an increase in the abundance of potential pathogens like Lachnospiraceae_NK4A136_group and Escherichia-Shigella. As a result, there were abnormal rises in lipopolysaccharide (LPS) levels in both colonic content and blood. Moreover, CAD treatment reversed the microbial dysbiosis and decreased the LPS levels induced by Mccp, thereby suppressing the activation of the TLR-4/NF-κB pathway and the Fas/FasL-caspase-8/-3 pathway. Consequently, this significantly mitigated the morphological and functional damage to the lungs and colons caused by Mccp. The findings offer novel insights and approaches for the clinical management of Mccp infections.